Family fortunes how to build family wealth and hold onto it for 100 years - Bonner, William, 1948- (Agora (Hoboken, N.J.), 2012)
"Advice on managing your wealth from bestselling author Bill BonnerFrom trusted New York Times bestselling author Bill Bonner comes a radical new way to look at family money and a practical, actionable guide to getting and maintaining multigenerational wealth. Family Wealth: How to Build a Family Fortune and Hold Onto It for 100 Years is packed with useful information, interwoven with Bonner's stories about his own family's wealth philosophy and practices.A comprehensive guide that shows how families can successfully preserve their estates by ignoring most of what people think they know about "the rich" and, instead, training and motivating all family members to work together toward a very uncommon goal. This book is a must-read for all individual investors--even those who do not plan to leave money to their children--because it challenges many of the most ubiquitous principles and rules of investing.You might expect a book on family wealth to be extremely conservative in its outlook. Instead, the Bonners announce what is practically a revolutionary manifesto. They explain: Why family money should NOT be invested in "safe, conservative" investments Why charitable giving is usually a waste of money, or worse Why it is NOT a good idea to let children go their own way Why you can't trust wealth "professionals" and why you should never entrust your money to money managers Why giving your children as much education as possible is NOT a good idea Why Warren Buffett and the rest of the rich people asking for higher tax rates are wrong to take "the pledge" Why Wall Street is a graveyard for capital, why most celebrity CEOs are a threat to the businesses they run, why modern capitalism is a failure, and more You will come away with a very different idea as to what family wealth is all about. It is not stodgy. Not boring. Not moss-backed and reactionary. On the contrary, it is the most dynamic, forward-looking capital in the world. The essential guide to passing wealth from one generation to the next, Family Wealth is filled with concrete, practical advice you can put to use right away"--